WiRoTip: an IoT-based Wireless Sensor Network for Water Pipeline Monitoring - Fatma Karray; Mariem Triki; Mohamed Wassim Jmal; Mohamed Abid; Abdulfattah M. Obeid (International Journal of Electrical and Computer Engineering (IJECE), 2018)
One of the key components of the Internet of Things (IoT) is the Wireless Sensor Network (WSN). WSN is an effective and efficient technology. It consists of senor nodes; smart devices that allows data collection and pre-processing wirelessly from real world. However, issues related to power consumption and computational performance still persist in classicalwireless nodes since power is not always available in application like pipeline monitoring. Moreover, they could not be usually suitable and adequate for this kind of application due to memory shortage and performance constraints. Designing new IoT WSN system that matches the application specific requirements is extremely important. In this paper, wepresent WiRoTip, a WSN node prototype for water pipeline application. An experimental and a comparative studies have been performed for the different node’s components to achieve a final adequate design.